Rola postrzegania duchowego w nauczaniu katechetycznym Jana Chryzostoma - Szczur, Piotr (Vox Patrum, 2014)
Among the works of John Chrysostom is twelve baptismal catecheses which he delivered most probably in Antioch. In these catecheses he tried to explain ceremonies connected with initiation. To realize his goal he appealed repeatedly to the sense of sight and he reminded catechumens/neophytes that everything they see has spiritual significance. This spiritual reality can be recognized by the organ, which he called “the eyes of the soul”, “spiritual eyes” or “the eyes of faith”. All of these terms denote a method of seeing what is invisible to the eyes of the body. In this way John Chrysostom equipped a neophyte with the eyes of faith able to induce the mind to create spiritual images of space. These images were meant to lead the physical feelings of catechumen/neophyte in the proper understanding of the rites of Christian initiation.